Destined - Cast, P. C. (Cast, P. C. House of night, 2011)
"Zoey is finally home where she belongs, safe with her Guardian Warrior, Stark, by her side, and preparing to face off against Neferet - which would be a whole lot easier if the High Counsel saw the ex-High Priestess for what she really is. Kalona has released his hold on Rephaim, and, through Nyx's gift of a human form, Rephaim and Stevie Rae are finally able to be together - if he can truly walk the path of the Goddess and stay free of his father's shadow... But there are new forces at work at the House of Night. An influx of humans, including Lenobia's handsome horse whisperer, threatens their precarious stability. And then there's the mysterious Aurox, a jaw-droppingly gorgeous teen boy who is actually more - or possibly less - than human. Only Neferet knows he was created to be her greatest weapon. But Zoey can sense the part of his soul that remains human, the compassion that wars with his Dark calling. And there's something strangely familiar about him... Will Neferet's true nature be revealed before she succeeds in silencing them all? And will Zoey be able to touch Aurox's humanity in time to protect him - and everyone - from his own fate? Find out what's destined in the next thrilling chapter of the House of Night series"--